Studi Pelapisan Dan Ketahanan Panas Coating Ni/Al Pada Baja Karbon Hasil Proses Elektroplating - Setiawan, Ahmad Sony (2016)
Carbon steel can find as a material of technique constraction, but the using of this material in high temperature into natural gas pipe, heat exchanger, it is really rare using this material in turbine component. Because the warm endurance of this carbon is really low. The purpose of this research is to develop intermetalic NI-AI layer to carbon steel by electroplating process, then knowing the micro structure, the glue of hardness mechanic and strength between coating and substrate. This research is using the low carbon steel ST 40 as a substrate with 16 mm diameter into 3 mm thickness and NI-AI chem as a layer material. It used 2.1 Volt for electroplating process during 2 hours immerse. The NI-AI layer is made into two variations namely 1 layer and two layers. Knowing the endurance of coating product, after electroplating specimen will be entered into pemenas oven by 700◦C temperature during 30 minutes. The characteristic of this product is doing by micro photo and the experiment of mechanic characteristic is doing by microvikers. It is for knowing the stern distribute and the glue strengthen coating. The research process result of electroplating NI/AI is only success for doing stell precipitate with NI layer. The result of thickness micro photo research NI for one layer and two layers, although it has been burned or it has contrarily. The result of this research shows that the electroplating thickness layer in the first precipitate during 7200 seconds, 0.016 Ampere with 19,78 µm thickness, meanwhile the electroplating result by using twice precipitate (2x7200 seconds) 0.019 Ampere has a result 24.98µm. next 0.025 Ampere has a result 27.24 µm. the hard research has done into the first result 128.5 HV, second 14.,3 HV, the third 160.2 HV, and fourth 163.5 HV, meanwhile in the research strengthen process into steel material with pressure energy 200 gf and it's during 10s, the result is 184.4 HV.